PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MEMBANGUN MINAT BERWIRAUSAHA MAHASISWA (Studi Kasus Mahasiswa Universitas Islam Riau) - Rosmita Ita; Nia Annisa Hidayati (UIR Press, 2022)
The study aims to see how entrepreneurial education can affect student entrepreneurship interests at the Islamic University of Riau. This type of study uses an associative survey. The study the associative survey is one that aims to establish links between two or more variables. Ultimately the result of this study explain causal connections between variables through hypothetical testing. Sampling taken from this study uses a non-sampling method with an incidental sampling technique. Data analysis on this study uses simple linear regression analysis. The study shows that variable X, which is entrepreneurial education with curriculum indicators, the quality of educators and teaching facilities, and the results of both category agreed-upon. As for the variable Y interest in self entrepreneurs, task and results oriented, taking risks, leadership, originality and forward oriented action, getting the results from those in the agreed category. The result of simple linear regression research suggests that entrepreneurial education has significant connections to student entrepreneurship interests.